Suppression of 5-lipoxygenase gene is involved in triptolide-induced apoptosis in pancreatic tumor cell lines - Zhou, G.X.; Ding, X.L.; Huang, J.F.; Zhang, H.; Wu, S.B. (Biochimica et biophysica acta, 2007)
Pancreatic adenocarcinoma is characterized by a poor prognosis and lack of response to conventional therapy. The purpose of this study was to investigate the effects of triptolide (TL) on proliferation and apoptosis of pancreatic cancer cells in vitro. We found that TL induced prominent growth inhibition and apoptosis in human pancreatic cell lines. In addition, TL treatment significantly down-regulated 5-lipoxygenase (5-LOX) expression, as well as downstream leukotriene B4 (LTB4) production, in these cell lines. Furthermore, overexpression of 5-LOX in SW1990 cell lines or exogenous LTB4 made them more resistant to TL-induced apoptosis, which was correlated with increased Bcl-2 expression. Taken together, these findings suggest that inhibition of the 5-LOX pathway of arachidonic acid metabolism is associated with the anti-proliferation activity of TL. We also provide evidence that TL has clinical therapeutic value for patients with pancreatic cancer.